2020
DOI: 10.1088/1367-2630/ab687a
|View full text |Cite
|
Sign up to set email alerts
|

Shapes of Fe nanocrystals encapsulated at the graphite surface

Abstract: We describe and analyze in detail the shapes of Fe islands encapsulated under the top graphene layers in graphite. Shapes are interrogated using scanning tunneling microscopy. The main outputs of the shape analysis are the slope of the graphene membrane around the perimeter of the island, and the aspect ratio of the central metal cluster. Modeling primarily uses a continuum elasticity (CE) model. As input to the CE model, we use density functional theory to calculate the surface energy of Fe, and the adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 55 publications
(93 reference statements)
1
36
0
Order By: Relevance
“…The extent of truncation is determined by the adhesion energy (β) between Cu(111) and MoS 2 (0001), and the surface energy (γ) of Cu(111), γ 111 . The procedure is described more fully elsewhere [20,24]. We use the value β = 0.874 J m −2 calculated with the van der Waals density functional (vdW-DF) known as vdW-DF2-B86R [14,25], for the above-mentioned (5 × 5)Cu(111)/(4 × 4)2h-MoS 2 (0001) coincidence lattice.…”
Section: Comparison With Equilibrium Crystal Shapementioning
confidence: 99%
“…The extent of truncation is determined by the adhesion energy (β) between Cu(111) and MoS 2 (0001), and the surface energy (γ) of Cu(111), γ 111 . The procedure is described more fully elsewhere [20,24]. We use the value β = 0.874 J m −2 calculated with the van der Waals density functional (vdW-DF) known as vdW-DF2-B86R [14,25], for the above-mentioned (5 × 5)Cu(111)/(4 × 4)2h-MoS 2 (0001) coincidence lattice.…”
Section: Comparison With Equilibrium Crystal Shapementioning
confidence: 99%
“…Recently, we have reported that high surface-to-volume ratios in metals can be achieved by encapsulating metal nanoclusters at the surface of a layered material, graphite. Effectively, the layered material resists deformation, thereby forcing the metal cluster between the layers to adopt a much flatter profile (higher aspect ratio) than it would otherwise [1,2]. Meanwhile the valuable properties of the metal may remain accessible or even be enhanced, e.g., in catalysis [3,4], magnetism [5], photonics [6], or other applications, despite being covered by a graphene layer(s).…”
Section: Introductionmentioning
confidence: 99%
“…The optB88-vdW functional [40] is used for electron-electron exchange correlations. This functional includes the vdW interactions, and its application for various vdW materials with metals [28][29][30][31][32][33][34][35][41][42][43] has already been proven very successful. A benchmark analysis for bulk properties of 6H-SiC and hexagonal close-packed (hcp) Dy is provided in Appendix A with the reasonable results.…”
Section: Dft Methodologymentioning
confidence: 99%
“…For multiple metal guest elements, it was recently demonstrated that it is difficult or impossible to directly penetrate the perfect TLG of graphite into the gallery beneath the TLG in the typical experimental temperature range <1500 K. This feature likely reflects a large energy barrier for the penetration. Thus, to effectively realize metal intercalation under the surface of graphite, a preprepared ion-bombarded graphite surface is always needed, where the guest metal atoms (e.g., Dy, Cu, Ru, Fe, and Pt) can intercalate through the portal defects [27][28][29][30][31][32][33][34][35]. However, previous experiments (including our own experiments for rare-earth metals Dy, Eu, and Gd [36,37]) show that many types of guest elements can intercalate into epitaxial graphene on a SiC substrate [4] without a preprepared ion-bombarded top surface.…”
Section: Introductionmentioning
confidence: 99%